COMPARISON OF INDONESIA'S EXPORT-IMPORT WITH CHINA AFTER THE AGREEMENT ON AGRICULTURE (AoA) - Setiawan, Mohamad Arief; Setiawan, Perdi; Kalfin, kalfin (iora, 2021)
The agricultural sector is the most important sector in the Indonesian and Chinese economies. The role of this sector is not only in international trade activities, but also plays a role in the domestic economy, including food sufficiency. The agricultural policies of Indonesia and China are not only oriented to increasing agricultural productivity for trade purposes but also to improving the standard of living of the people, especially farmers. The flow of economic liberalization brought by the World Trade Organization (WTO) has become a dilemma for Indonesian and Chinese agriculture. On the one hand, the WTO accession decision opens access to wider international trade, but on the other hand, both countries must protect their agriculture through the determination of prices for agricultural products by the government. This paper aims to find out the comparison of Indonesia's exports and imports with China in the field of trade in agricultural products after the implementation of the Agreement on Agriculture (AoA) or agricultural agreements which are part of the WTO from January 1, 1995, to the present. The results of the study obtained that the comparison of Indonesia's exports and imports with China was more optimal. From the research results, it can be used as a comparison for the government in determining further policies to get maximum results.